2020
DOI: 10.3390/ani10040734
|View full text |Cite
|
Sign up to set email alerts
|

Increase in Milk Yield from Cows through Improvement of Forage Production Using the N2-Fixing Legume Leucaena leucocephala in a Silvopastoral System

Abstract: The objective was to evaluate milk production, N2-fixation and N transfer, forage yield and composition (under two cutting intervals) in a silvopastoral system (SPS) with Leucaena leucocephala-Megathyrsus maximus and M. maximus-monoculture (MMM) with crossbred cows in a completely randomized design. Forage yield in the SPS was 6490 and 6907 kg DM ha−1 for cutting intervals (CI) of 35 and 50 days. Forage yield for the MMM was 7284 and 10,843 kg DM ha−1, and forage crude protein (CP) was 29.0% and 26.1% for L. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
2
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
6
2
1
Order By: Relevance
“…Results on chemical composition differ from those found by other authors, who suggested a higher nutritional quality in the ISPS due to the effects of shade and nitrogen fixed by tree legumes [14,23,68,69]. Shelton and Dalzell (2007) [70] reported that leucaena forage contains 20% crude protein, is highly digestible, and provides a consistently highquality diet throughout the year.…”
Section: Dry Matter Yield and Chemical Composition Of Pasturecontrasting
confidence: 76%
See 1 more Smart Citation
“…Results on chemical composition differ from those found by other authors, who suggested a higher nutritional quality in the ISPS due to the effects of shade and nitrogen fixed by tree legumes [14,23,68,69]. Shelton and Dalzell (2007) [70] reported that leucaena forage contains 20% crude protein, is highly digestible, and provides a consistently highquality diet throughout the year.…”
Section: Dry Matter Yield and Chemical Composition Of Pasturecontrasting
confidence: 76%
“…ISPSs provide environmental services such as erosion control, watershed protection, carbon sequestration (27-163% more than monoculture systems, MS), reductions in methane emissions, atmospheric nitrogen fixation, reductions in biodiversity loss, and modifications of the microclimate improving animal welfare [13,15,[18][19][20][21]. Overall, ISPSs have been reported to be more productive at animal (e.g., higher milk and beef yield) and pasture levels (32% higher dry matter production [22]) per unit of area compared with conventional or monoculture livestock systems [15,[22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…In tropical and subtropical conditions, legumes such as Desmodium ovalifolium, Leucaena leucocephala, Centrosema pubescens, Stylosanthes guianensis, Cajanus cajan, among others, can fix between 120 and 150 kg N/ha/yr. For SPS with Leucaena leucocephala planted in rows in Australia, nitrogen fixation rates range between 36 and 61.9 kg/ha/y (Radrizzani et al, 2011;Conrad et al, 2018) while for an iSPS with high density of L. leucocephala in Mexico ranged between 77.1 and 80 kg N/ha over a period of 100 days (Sarabia-Salgado et al, 2020). This fixed N becomes available slowly over time to the grass in pastures after its release into soil via exudates from living legume roots, by mineralization of senesced legume tissues and in excreta after consumption by grazing animals (Ledgard et al, 2009), generating lower losses of N that can be converted into N 2 O (Schmeer et al, 2014).…”
Section: Legumes As An Alternative To N Fertilizermentioning
confidence: 99%
“…Silvopastoral systems, proposed by all initiatives, intrinsically contribute to circularity, as the whole system is based on taking advantage of the internal nutrient recycling processes occurring between trees, shrubs, pastures, and animals to minimize the use of external inputs [41,49]. For instance, in silvopastoral systems, nitrogen-fixing shrubs such as Leucaena leucocephala can fix atmospheric nitrogen at rates ranging from 77 kg ha -1 to 250 kg ha-1 [50,51]. Phosphorus, a limiting mineral in most acidic tropical soils due to Al and Fe immobilization can be solubilized and made available for plant uptake when the mycorrhiza and microbiota related to specific trees and shrubs are planted in high densities [52].…”
Section: Input Circularity-fertilizersmentioning
confidence: 99%